Resources and bridging: the role of spatial context in rural entrepreneurship - Müller, Sabine; Korsgaard, Steffen (Entrepreneurship and regional development, 2018)
This article contributes to the emerging discussion on the role of context in entrepreneurship as well as the development of theorizing on rural entrepreneurship. It does so by exploring the role of spatial context for rural entrepreneurs. Through a case study of 28 ventures, two modes of spatializing rural entrepreneurial activities are identified in the form of resource endowments and spatial bridging. Additionally, we develop a typology of rural entrepreneurs, which captures hitherto unexplored heterogeneity within this group of entrepreneurs. Spatial context is found to be of considerable significance to the rural entrepreneurial process and hence this study contributes to a micro-level understanding of place-specific entrepreneurial practices and the non-local circulation of value that can enrich local economies.